High-frequency conversion to a "fluffy" developmental phenotype in Aspergillus spp. by 5-azacytidine treatment: evidence for involvement of a single nuclear gene. - Tamame, M (1983)
Transient exposure of mycelia from Aspergillus niger and Aspergillus nidulans to the cytidine analog 5-azacytidine, leading to no more than 0.3 to 0.5% substitution for cytosine by 5-azacytosine in A. nidulans DNA, resulted in the conversion of a high fraction of the cell population (more than 20%) to a mitotically and meiotically stable "fluffy" developmental phenotype. The phenotypic variants are characterized by the developmentally timed production of a profuse fluffy network of undifferentiated aerial hyphae that seem to escape signals governing vegetative growth. Genetic analysis with six different fluffy clones reveals that this trait is not cytoplasmically coded, is recessive in heterozygous diploids but codominant in heterokaryons, and exhibits a 1:1 Mendelian segregation pattern upon sexual sporulation of heterozygous diploids. Complementation and mitotic haploidization studies indicated that all variants are affected in the same gene, which can be tentatively located on chromosome VIII of A. nidulans. Molecular analysis to search for modified bases showed that DNA methylation is negligible in in both A. niger and A. nidulans and that no differences could be detected among DNAs from wild-type cells, fluffy clones, or mycelia exposed to 5-azacytidine. It thus appears that high-frequency conversion of fungal mycelia to a stable, variant developmental phenotype by 5-azacytidine is the result of some kind of target action on a single nuclear gene and that this conversion can occur in organisms virtually devoid of DNA methylation.